2009
DOI: 10.2741/3228
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the nitric oxide signaling pathway and targets for drug development

Abstract: Nitric oxide is a multifunctional signaling molecule, intricately involved with maintaining a host of physiological processes including but not limited to host defense, neuronal communication and the regulation of vascular tone. Many of the physiological functions first ascribed to NO are mediated through its primary receptor, soluble guanylyl cyclase. Endogenous production of NO is a highly complex and regulated process involving the 5-electron oxidation of L-arginine requiring numerous substrates and cofacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
165
0
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(184 citation statements)
references
References 179 publications
0
165
0
14
Order By: Relevance
“…The NOS pathway is ubiquitous in the adult mammal, with endothelial, neuronal, and inducible NOS isoforms playing critical roles in every organ system, in particular cardiovascular homeostasis, thrombosis, neurotransmission, and immunity [ 24 ]. With respect to vascular reactivity and structure, NO plays a dominant role as a vasodilation factor that also potently inhibits vascular smooth muscle proliferation, leukocyte infi ltration, and platelet adherence and aggregation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOS pathway is ubiquitous in the adult mammal, with endothelial, neuronal, and inducible NOS isoforms playing critical roles in every organ system, in particular cardiovascular homeostasis, thrombosis, neurotransmission, and immunity [ 24 ]. With respect to vascular reactivity and structure, NO plays a dominant role as a vasodilation factor that also potently inhibits vascular smooth muscle proliferation, leukocyte infi ltration, and platelet adherence and aggregation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three NOS isoforms have been identified and distinguished by their tissue distribution: neuronal (nNOS), inducible (iNOS), and endothelial (eNOS). The nNOS (Type I) is located in a discrete neuronal populations of the central (CNS) and peripheral (PNS) nervous system; the iNOS (Type II) is expressed by different cell types in response to inflammatory stimuli; the eNOS (Type III) has been identified in endothelial cells and astrocytes (Garthwaite, 1991;Bredt and Snyder, 1992;Dawson and Dawson, 1996;Moncada et al, 1997;Bredt, 1999;Davis et al, 2001;Ahern et al, 2002;Calabrese et al, 2007;Bryan et al, 2009). Interestingly, the nNOS is also present in macrophages and endothelial cells, in which it is probably involved in the basal modulation of vascular tone (Seddon et al, 2008).…”
mentioning
confidence: 99%
“…Two of these are constitutive enzymes (neuronal NOS or NOS-I and endothelial NOS or NOS-III) requiring intracellular Ca ++ accumulation and are expressed in many cell types within the ocular compartment, 14 whereas the third isoform (NOS-II or iNOS) is mainly expressed in immune cells, is induced in response to pro-inflammatory stimuli, and produces large amounts of NO in a Ca ++ -independent manner. 14,15 It has been reported that a low physiological amount of NO activates soluble guanylyl cyclase and vascular relaxation, 15,16 favors neuronal transmission, and modulates gene transcription through nuclear factor NF-kappa B signaling. 17,18 Conversely, large quantities are thought to result in abnormal neuronal activity and central sensitization, 19 activate proinflammatory cytokines, and promote tissue-specific oxidative and nitrosative stress.…”
Section: Introductionmentioning
confidence: 99%